Remembering Lucile: a Virginia family's rise from slavery and a legacy forged a mile high - McLean, Polly E. Bugros, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
The University of Colorado erroneously recognized Dr. Ruth Cave Flowers as its first Black graduate. In 1918--six years before Flowers's graduation--Lucile Berkeley Buchanan Jones received her bachelor's degree. McLean introduces this woman who lived through an extraordinary time and rectifies the omission from institutional history.--Provided by publisher.
Prologue: her voice can be heard -- Inquiry and epiphany -- Born in slavery: the master, the mistress, and their chattel -- The Berkeleyes: a slave named Harriet Bishop, and her daughter, Sarah -- Slavery's chain done broke at last -- Colorado and the promise of freedom -- From Denver's bottoms to P.T. Barnum's town -- Education, politics and leisure -- The frontier in our souls -- School, community, and love lost -- A fly in the buttermilk: Colorado and the world of higher education -- "Goin' to Kansas City": education and baseball -- It's Mister Jones, if you please! -- Chicago, take two -- "Lincoln was a Republican, that's all I need to know!" -- Coming home and going home -- Epilogue: the end of the living line.
Keywords: Jones, Lucile Berkeley Buchanan, -- 1884-1989 -- Biography; University of Colorado Boulder -- Students -- Biography; Children of freedmen -- Biography